(untitled) (Bangladesh Journal of Medical Science, 2024)
The aim of the study to develop a methodology for improving the level of development of the coordination abilities of mentally retarded children aged 8-9 years in the lessons of adaptive physical education. Methods The study was organized at a special correctional school from September 13 to December 16, 2023. 14 schoolchildren aged 8-9 took part in the experiment. Children from the control group studied according to the usual program, and children from the experimental group performed complexes of coordination exercises and used outdoor games during lessons on adaptive physical culture. The level of development of coordination abilities of mentally retarded children aged 8-9 years was determined by three tests: 3x10m shuttle run, one-leg stand, obstacle course. The Student’s T-Test was the main method of mathematical processing of the research results. Results Prior to the start of the study, the difference in performance in control tests in both groups was not significant and not reliable (p>0.05), which indicates the homogeneity of the groups. After the end of the pedagogical experiment, the indicators of coordination abilities of children from the control group improved, but not significantly or significantly (p>0.05). Significant positive changes occurred in the experimental group for all tests. In the shuttle run, the indicators became higher by 0.5 seconds (p>0.05), in the one-leg stand test, the indicators improved by 1.1 seconds (p>0.05), and in the obstacle course test, the indicators improved by 1.2 seconds (p<0.05). An intergroup comparison showed a difference in two of the three indicators of coordination abilities when the significant difference is the shuttle run (p<0.05) and the obstacle course (p<0.05). Conclusion The developed experimental methodology for the development of coordination abilities for mentally retarded children aged 8-9 years in the lessons of adaptive physical education has proven its effectiveness and is recommended for use in correctional schools in working with mentally retarded children. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1219-1226